THE IMPACT OF QUANTUM TECHNOLOGIES ON HEALTHCARE - G. E. Nurmetova; M. Sh. Ollamberganova (Web of Journals Publishing, 2024)
Quantum medicine is a gentle, painless, therapeutic, stimulation of human or animal cells in biologically active points and zones with small doses of natural radiation and fields for the speedy return of the body from a state of illness to a stable healthy state and maintenance of such a state for a long time. An analytical review of the results of the current state of the AP is provided equipment for the treatment, diagnosis, prevention and rehabilitation of patients, due to the targeted effect of low doses of electromagnetic radiation. The effectiveness and safety of this type of equipment is justified. The basic principles of quantum therapy; quantum therapy devices; advantages of quantum medicine. Quanta - the smallest particles of energy have permeated the entire Earth with all its inhabitants since the very beginning of time. We all swim in the ocean of quanta. Humanity realized this fact relatively recently about a hundred years ago. At the beginning of the 20th century, a new science appeared quantum physics. Quantum diagnostics is because the energy-informational parameters of an organism in a definite and unambiguous way characterize the state of both the organism as a whole and its individual organs, systems and connections. By measuring the corresponding electrical parameters at certain points on the surface of the patient's body, it is possible to reliably assess the functional state of the body, identify a specific disease, and identify the occurrence of pathological processes at an early stage and the presence of a predisposition of the patient's body to certain types of diseases. Quantum therapy uses environmentally friendly types of electromagnetic radiation in order to restore the electromagnetic information field of the patient distorted by the disease and transfer it to a stable state of health. In the treatment of patients, a large statistical material has been accumulated on the effectiveness of quantum therapy, which allows using this method in almost all fields of medicine: cardiology, gastroenterology, pulmonology, dentistry, orthopedic traumatology, surgery, sports medicine, gynecology, cosmetology, neurology, dermatology, and urology. It is important to emphasize that quantum therapy is increasingly being used in the treatment of diseases such as cancer and radiation sickness. Diseases of the musculoskeletal system, cerebral palsy, bronchial asthma, alopecia, enuresis, infertility.
Keywords: Quantum, therapy, devices, healthcare.